Molecular symmetry in chemistry via group theory - Agarwala, U. C., author; Nigam, H. L., author; Agrawal, Sudha, author; Kalra, S. S., author (New Delhi : Ane Books Pvt. Ltd., 2013)
Includes bibliographical references and index